2020
DOI: 10.1097/pgp.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

HPV-negative Tumors in a Swedish Cohort of Cervical Cancer

Abstract: Despite the common perception that the human papilloma virus (HPV) is a requirement for the development of cervical cancer (CC), a considerable number of CCs test HPV negative. Presently, many countries are shifting to HPV primary CC screening, and it is of importance to increase the knowledge about the group of CCs that test HPV negative. The aim of this study was to reinvestigate a proportion of cervical tumors with a primary negative or invalid test result. Reinvestigation with repeated genotyping (targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 35 publications
2
32
2
1
Order By: Relevance
“…The increase in the rates of HPV negative and HPV untypable specimens during the period of 2010–2019 in our study is puzzling. As reported by several studies, the prevalence of HPV negative specimens among women with abnormal pap smears, CIN or invasive cervical cancer is about 12–14% [ 24 , 25 ], a rate that is comparable to our data. Interestingly Petry et al reported that HPV-negative status in cervical cancer could be a false diagnosis or false-negative HR-HPV results, caused by use of HC2 method [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The increase in the rates of HPV negative and HPV untypable specimens during the period of 2010–2019 in our study is puzzling. As reported by several studies, the prevalence of HPV negative specimens among women with abnormal pap smears, CIN or invasive cervical cancer is about 12–14% [ 24 , 25 ], a rate that is comparable to our data. Interestingly Petry et al reported that HPV-negative status in cervical cancer could be a false diagnosis or false-negative HR-HPV results, caused by use of HC2 method [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among our patients with negative HPV PCR results, 8 of 9 had positive p16 expression. This contradictory pattern has been described in other studies which found the initial HPV PCR negativity – with p16 positive IHC – reduced from 19/209 to 5/209 cervical carcinomas after expanding molecular studies (targeting E6/E7 genes) 36 . The p16 positivity is therefore considered a more sensitive indicator of HPV-mediated carcinogenesis in cervical cancers.…”
Section: Discussionmentioning
confidence: 59%
“…Screening and management of precancerous lesions contribute to the prognosis of CC, whereas HPV vaccinations prevent infection from certain strains of HPV; however these preventative measures have limitations (30). For example, a considerable number of CCs have been confirmed to be HPV negative (31). As aforementioned, TMP was found to serve an inhibitory role in numerous types of cancer (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%